SUBSTITUSI TERIGU DENGAN TEPUNG LABU KUNING TERHADAP SIFAT FISIK DAN ORGANOLEPTIK MUFFIN - Budoyo, Edwin Aleksander Septian; Suseno, Thomas Indarto Putut; Widjajaseputra, Anna Ingani (Jurnal Teknologi Pangan dan Gizi, 2014)
Muffin is one of the preferred foods by all groups of ages. Basically, wheat flour which is used in the muffin manufacturing are the medium flour and weak flour. Muffin is potential to be substituted with low protein flour such as pumpkin flour. Pumpkin flour has a different characteristic with wheat flour such as sugar content, fiber and carotenoid. Those component can determine muffin’s physical properties such as color, browning, flavor, and organoleptic so it is important to determine the effect of substitution to the muffin’s physical and organoleptic properties. The raw material used in this study are pumpkin flour and medium wheat flour. Other ingredients are butter, sugar, eggs, skim milk, vanilla and baking powder. Used research design was Randomized Block Design (RDB) with a single factor, namely the level of substitution of wheat flour by pumpkin flour with seven levels 0%, 5%, 10%, 15%, 20%, 25% and 30% with four replications. The tested parameters were water content, water activity, volume expansion, texture (hardness, springiness, cohesiveness and chewiness), and organoleptic test (color, texture and flavor). Substitution of wheat flour with pumpkin flour influences the water content, water activity, volume expansion, hardness, springiness, chewiness and organoleptic test (color, texture and flavor) with significance level α=5%, but the substitution doesn’t influence cohesiveness. The optimal substitution level is 15%.